Insights Into Drug Resistance in Staphylococcus aureus - Aqib, Amjad (Infectious Diseases, 2021)
Staphylococcus aureus is a coccus, gram-positive, non-spore forming, and non-motile bacterium. Its commensal and opportunistic capabilities make it able to colonize different sites of animals and humans. Resistance to antibiotics has resulted in development of new strains and new types within strains. Types of methicillin-resistant S. aureus (MRSA) include hospital-acquired MRSA (HA-MRSA), community-acquired MRSA (CA-MRSA), and livestock-acquired MRSA (LA-MRSA). There are also new strains like vancomycin-resistant S. aureus (VRSA) and vancomycin-intermediate S. aureus (VISA). Expansion in resistance is expected to give rise to newer strains resistant to antibiotics such as macrolide (erm gene), tetracycline (tet genes), mupirocin (mupR), and fusidic acid (fusD). Alternative approaches like nanoparticles, bacteriophages, phytochemicals, and more are required to tackle this pathogen. This book contains information on epidemiology, resistance mechanisms, and alternative ways to curtail S. aureus infection, as well as future research opportunities.